Environmental impact assessment in Mexico: an analysis from a ‘consolidating democracy’ perspective - Palerm, Juan; Aceves, Carla (My University, 2004)
Although Mexico has nominally been a democracy for nearly a century, it may at best be described as a ‘consolidating’ democracy. This status of the political system is clearly reflected in its EIA legislation, particularly with regard to the ‘participatory’ and ‘pluricultural’ dimensions, which relate, in broad terms, to an incipient civil society, limited public participation and inadequate integration of indigenous peoples. This paper analyses Mexico's EIA legislation under these two dimensions of democracy and makes recommendations on how it should be amended to respond to the challenges of a consolidated democratic system, such as: broadening opportunities for public participation; making the system more accountable; and seeking legitimate means to integrate indigenous peoples and traditional knowledge in the EIA process. © Impact Assessment and Project Appraisal
Keywords: Environmental impact assessment; Consolidating democracy; Emerging democracy; Environmental decision-making; Public participation